'Dutch don't dance' – leisure experiences and sense of belonging among Polish migrants in the Netherlands. Issue 3 (4th May 2018) - Peperkamp, Esther
Abstract: The influx of migrants in Western Europe raises questions about the potential of leisure spaces and activities to support processes of social inclusion and to allow migrants to develop a sense of belonging. Discussions are ongoing about how this potential is realised or not. In this paper, I propose that the perspective of leisure activities as ritual may help to untangle how leisure spaces and practices build solidarity and a sense of belonging. The paper draws on interviews with Polish migrants to the Netherlands about leisure activities they undertake. Specifically, the paper will examine dance clubs as spaces and going out as activity in which migrants enter into contact with locals. It will show how these spaces and activities ultimately fail as potential sites for developing a sense of belonging.